The Role Of Strategic Planning As One Of The Management Factors In Improving The Market Share Of Medium Projects (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to identify the relationship between strategic planning and market share in medium projects in Lattakia governorate, by knowing the impact of vision, mission and goals. The researcher relied on the deductive approach as a general approach to research, followed the survey methodology, distributed the questionnaire to 395 staff of the project staff, and then conducted a field study for the purpose of demonstrating this relationship. The study concluded that there is an acceptable positive correlation between strategic planning and market share. Then, he presented a summary of the most important results reached, where the most important main result is a great role for strategic planning in improving market share through vision, mission and goals, and then presented some suggestions and recommendations to improve the relationship The most important of which is: giving more attention to the strategic planning function and the importance of convincing senior management in medium projects of the importance of developing strategic dimensions through the formation of an independent strategic management in medium projects with the work to provide them with cadres and competencies capable of making strategic decisions and the development of appropriate strategic plans and the implementation of activities and adoption of various Planning methods and contribute to the creation of strategic awareness among all dealers in the light of the various environmental conditions surrounding.